La sensorialité olfactive du paysage, médiatrice d’une reliance sensible - Victor Fraigneau (VertigO)
The experience of a space or place affects us much more than just through our auditory and visual senses: smelling, for instance, makes us feel the rhythm of the landscapes and environments we inhabit. We can then specify the definition of olfactory landscapes. The methodologies to understand the sensitive landscape explore the reception and expression of the landscape olfactory dimension. Smells express cultural, historical and geographical values, they relate the experience of a place, a city or a territory. The sense of smell, personal and subjective, constitutes a vector of territory attachment. The study of its reception modes informs us of its intimate and shared perception. It can be appreciated as an example of a “reliance” in that it actively binds us to the world. This article thus introduces the notion of “reliance” as including the activating relationships of attachment and sharing. This relationship, which illustrates a sensitive link to the landscape, defines itself as complex. Such an approach leads to question how considering the olfactory characteristics of our environments and their sources warns us of their ecological importance and influences our perception in a truly sensitive way.